Revision of the subgenus Hemiglaphyrus Champenois, 1903 of Glaphyrus Latreille, 1807, with description of three new species and Atticoglaphyrus new subgenus (Coleoptera: Glaphyridae) - Ghrejyan, Tigran; Kalashian, Mark; Sabatinelli, Guido (Zootaxa, 2023)
The subgenus Hemiglaphyrus Champenois, 1903 of Glaphyrus Latreille, 1807 is revised. It currently includes four species: G. (H.) caucasicus Kraatz, 1882 (type species), G. (H.) armeniacus Ghrejyan, Kalashian & Sabatinelli, new species from Armenia, G. (H.) urartu Sabatinelli, Ghrejyan & Kalashian, new species from East Turkey and Iran and G. (H.) schweigeri Ghrejyan, Kalashian & Sabatinelli, new species from Iran and Iraq, here described and illustrated. A key to Hemiglaphyrus species is provided. Atticoglaphyrus Ghrejyan, Kalashian & Sabatinelli, new subgenus is established for G. modestus Kiesenwetter, 1858 originally included in Hemiglaphyrus. Lectotypes of Glaphyrus caucasicus Kraatz, 1882 and Glaphyrus modestus Kiesenwetter, 1858 are designated.